Self‐Concepts, Self‐Esteem, and Academic Achievement of Minority and Majority North American Elementary School Children. Issue 4 (7th April 2017) - Cvencek, Dario; Fryberg, Stephanie A.; Covarrubias, Rebecca; Meltzoff, Andrew N.
Abstract : Minority and majority elementary school students from a Native American reservation ( N  = 188; K–fifth grade; 5‐ to 10‐year‐olds) completed tests of academic self‐concepts and self‐esteem. School grades, attendance, and classroom behavior were collected. Both minority and majority students exhibited positive self‐esteem. Minority students demonstrated lower academic self‐concepts and lower achievement than majority students. Two age‐related patterns emerged. First, minority students had lower academic achievement than majority students, and this effect was stronger in older (Grades 3–5) than in younger (Grades K–2) students. Second, children's actual achievement was related to their academic self‐concepts for older students but more strongly linked to self‐esteem in younger students. The authors offer a developmental account connecting students' developing self‐representations to their school achievement.